A New We - Stefan Wolf (Love Production, 2010)
The filmmaker traveled through Europe in order to explore and document well established eco-communities that portray some of the broad spectrum of lifestyle possibilities that are part of our global effort to transition to a sustainable world. The lives shown here are more motivated by imagination, vision, respect and cooperation than by economic forces and social expectations. In these 10 communities, the creative solutions to many social, environmental and economic challenges exemplify the nearly infinite capacity for human-, community- and self-development.